Les différentes facettes de l’interactionnisme socio-discursif - Jean-Paul Bronckart (Calidoscópio, 2010)
The author locates the socio-discursive interactionism (SDI) in relation to the multiple paradigms within the social and human sciences, demonstrating that his theory is an attempt towards the extension and development of the social interactionist project, started in the first three decades of the 20th century. His work is developed according to three objectives: a) to present the fundamental orientations in the construction of SDI, which has been the aim of his work for the past 30 years; b) to present five empirical research orientations, which have been developed from SDI; c) to evoke some new perspectives for future theoretical development. Key words: socio-discursive interactionism, research orientations, new perspectives.